39th Winter School on Vibroacoustical Hazards Suppressions Szczyrk, Poland, February 28 – March 4, 2011 - BUKOWSKI, Roman (Archives of Acoustics, 2011)
Traditionally I invite you to acquaint with the preliminary list of lectures and someabstracts of lectures submitted for presentation in the 39th Winter School on VibroacousticalHazards Suppressions. This national School, organized by Upper Silesian Divisionof the Polish Acoustical Society and Institute of Physics at the Silesian Universityof Technology, is planned this year at the turn of February and March 2011. This conferenceis organized in different places of Silesian Beskidy Mountains, but this year willbe again organized in Szczyrk.The conference is the forum for all environmental vibroacoustics fields. Particularlyit concerns the traffic noise, industry noise, vibroacoustics of machines, room acoustics,noise protection and similar problems. During the School, the theoretical works, experimental,measuring, technical, applied and normative ones are presented.The School lectures, and other conference materials, will be published in the “Materialsof the XXXVIX Winter School on Vibroacoustical Hazards Suppressions” (inPolish) edited by dr. Roman Bukowski and dr. Mieczysław Roczniak (chairman of theconference). This publication is intended for participants of the School and for manylibraries in Poland.